Effect of microclimate on the performance of salad cucumber under naturally ventilated polyhouse - PREENU N. P; Dr. K. V Levan (Guide) (Tavanur 2014 DEPARTMENT OF IRRIGATION AND DRAINAGE ENGINEERING)
Effect of microclimate on the performance of salad cucumber under naturally ventilated polyhouse
Effect of microclimate on the performance of salad cucumber under naturally ventilated polyhouse